Invasive fungal disease in patients undergoing umbilical cord blood transplantation after myeloablative conditioning regimen. (12th February 2019) - Montoro, Juan; Sanz, Jaime; Lorenzo, José I.; Montesinos, Pau; Rodríguez‐Veiga, Rebeca; Salavert, Miguel; González, Eva; Guerreiro, Manuel; Carretero, Carlos; Balaguer, Aitana; Gómez, Inés; Solves, Pilar; et al.
Abstract: Objective: Characteristics and risk factors (RFs) of invasive fungal disease (IFD) have been little studied in the setting of umbilical cord blood transplantation (UCBT). Method: We retrospectively included 205 single‐unit myeloablative UCBT recipients with a median follow‐up of 64 months. Results: Fifty‐six episodes of IFD were observed in 48 patients (23%) at a median time of 123 days after stem cell infusion. Invasive mold disease (IMD) occurred in 42 cases, 38 of them (90%) caused by invasive aspergillosis whereas invasive yeast disease (IYD) occurred in 14 cases, most of them due to candidemia (n = 12, 86%). The 5‐year cumulative incidence of IFD, IMDs, and IYDs was 24% 19%, and 7%, respectively. In multivariate analysis, three RFs for IMDs were identified: age >30 years (HR 3.5, P  = 0.017), acute grade II‐IV graft‐versus‐host disease (HR 2.3, P  = 0.011), and ≥1 previous transplant (HR 3.1, P  = 0.012). The probability of IMDs was 2.5%, 14%, and 33% for recipients with none, 1, or 2‐3 RFs, respectively ( P  < 0.001). Among IFD, IMDs had a negative effect on non‐relapse mortality in multivariate analysis (HR 1.6, P  = 0.039). IMDs showed a negative impact on overall survival (HR 1.59, P  = 0.018). Conclusion: Invasive mold disease were very common and serious complication after UCBT.